WEBVTT
00:00:01.350 --> 00:00:12.140
Subtract seven 𝑦 plus 𝑧 squared minus three 𝑥 cubed from six 𝑥 cubed plus five 𝑧 squared minus eight 𝑦.
00:00:14.000 --> 00:00:19.890
In order to subtract these two expressions, we need to group or collect the like terms.
00:00:21.200 --> 00:00:24.090
Firstly, we can group the 𝑥 cubed terms.
00:00:24.440 --> 00:00:36.540
Six 𝑥 cubed minus negative three 𝑥 cubed, this is equal to nine 𝑥 cubed as six minus negative three is equal to nine.
00:00:37.910 --> 00:00:40.040
Next, we can group the 𝑦 terms.
00:00:40.480 --> 00:00:51.870
Negative eight 𝑦 minus seven 𝑦, this is equal to negative 15 𝑦 as negative eight minus seven is equal to negative 15.
00:00:53.370 --> 00:00:57.560
Finally, we need to group the 𝑧 or 𝑧 squared terms.
00:00:58.070 --> 00:01:08.660
Five 𝑧 squared minus 𝑧 squared, this is equal to four 𝑧 squared as five minus positive one is equal to four.
00:01:10.130 --> 00:01:28.740
This means that our answer when we subtract seven 𝑦 plus 𝑧 squared minus three 𝑥 cubed from six 𝑥 cubed plus five 𝑧 squared minus eight 𝑦 is equal to nine 𝑥 cubed minus 15 𝑦 plus four 𝑧 squared.